2021
DOI: 10.3390/jcs5020043
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hybrid Nano-Zinc Oxide and Cellulose Nanocrystals on the Mechanical, Thermal, and Flammability Properties of Poly (Lactic Acid) Polymer

Abstract: Biopolymers with universal accessibility and inherent biodegradability can offer an appealing sustainable platform to supersede petroleum-based polymers. In this research, a hybrid system derived from cellulose nanocrystals (CNCs) and zinc oxide (ZnO) nanoparticles was added into poly (lactic acid) (PLA) to improve its mechanical, thermal, and flame resistance properties. The ZnO-overlaid CNCs were prepared via the solvent casting method and added to PLA through the melt-blending extrusion process. The composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Bajwa et al successfully prepared Pt/ZnO hollow birdcage-like special structure by reacting H 2 PtCl 6 with zinc salt [ 2 ]. Harini et al successfully synthesized petal-like nano-ZnO at low temperature by using zinc sulfate and sodium hydroxide as raw materials and adding cationic surfactants.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Bajwa et al successfully prepared Pt/ZnO hollow birdcage-like special structure by reacting H 2 PtCl 6 with zinc salt [ 2 ]. Harini et al successfully synthesized petal-like nano-ZnO at low temperature by using zinc sulfate and sodium hydroxide as raw materials and adding cationic surfactants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…And electron-hole pairs generally have picosecond lifetime, sufficient to allow photogenerated electrons and photogenerated hole pairs to transfer charge via the band gap to materials adsorbed on the semiconductor surface from the solution or gas phase. e overall reaction process of photocatalytic degradation of organic pollutants by semiconductor photocatalyst can be represented by equation (2).…”
Section: Photocatalysis Of Nano-zincmentioning
confidence: 99%
“…The main decomposition step occurred at higher temperatures (300–450 °C), with the cleavage of the main lignin chain, and was followed (above 500 °C) by several rearrangements and condensation reactions of the aromatic structure that leads to the formation of char structures [ 32 , 33 ]. The degradative path of ZnO@LNP was similar, with a slight shift toward higher temperature for the initial degradation events, a lower degradation rate related to the main, but a lower peak temperature (400 and 413 °C, respectively for ZnO@LNP and LNP), which was essentially related to the catalytic role of ZnO-NP nanoparticles at high temperature [ 34 ]. The degradation in the oxidative environment (not shown here) confirmed that 4 wt % of ZnO was found on the LNP surface.…”
Section: Resultsmentioning
confidence: 99%
“…Bajwa et al investigated the action of hybrid filler based on cellulose nanocrystal (CNC) and zinc oxide (ZnO) to improve mechanical, thermal, and flame resistance properties of melt-blending extrusion poly(lactic acid) (PLA) nanocomposites. The authors pointed out the increase in the mechanical, thermal, and flame retardancy properties [7]. Leite et al studied the gelatin films incorporated with CNC.…”
Section: Introductionmentioning
confidence: 99%